Clinical effectiveness, cost-effectiveness and process evaluation of group schema therapy for eating disorders: study protocol for a multicenter randomized controlled trial - Suzanne H. W. Mares; Jeffrey Roelofs; Janôt Zinzen; Manouk Béatse; Hermien J. Elgersma; Ruben M. W. A. Drost; Silvia M. A. A. Evers; Annemarie A. van Elburg (BMC Psychology, 2024)
Abstract Background Eating disorders (EDs), such as (atypical) Anorexia (AN) and Bulimia Nervosa (BN), are difficult to treat, causing socioeconomic impediments. Although enhanced cognitive behavioral therapy (CBT-E) is widely considered clinically effective, it may not be the most beneficial treatment for (atypical) AN and BN patients who do not show a rapid response after the first 4 weeks (8 sessions) of a CBT-E treatment. Alternatively, group schema therapy (GST) may be a valuable treatment for this ED population. Even though GST for EDs has yielded promising preliminary findings, the current body of evidence requires expansion. On top of that, data on cost-effectiveness is lacking. In light of these gaps, we aim to describe a protocol to examine whether GST is more (1) clinically effective and (2) cost-effective than CBT-E for (atypical) AN and BN patients, who do not show a rapid response after the first 4 weeks of treatment. Additionally, we will conduct (3) process evaluations for both treatments. Methods Using a multicenter RCT design, 232 Dutch (atypical) AN and BN patients with a CBT-E referral will be recruited from five treatment centers. Clinical effectiveness and cost-effectiveness will be measured before treatment, directly after treatment, at 6 and at 12 months follow-up. In order to rate process evaluation, patient experiences and the degree to which treatments are implemented according to protocol will be measured. In order to assess the quality of life and the achievement of personalized goals, interviews will be conducted at the end of treatment. Data will be analyzed, using a regression-based approach to mixed modelling, multivariate sensitivity analyses and coding trees for qualitative data. We hypothesize GST to be superior to CBT-E in terms of clinical effectiveness and cost-effectiveness for patients who do not show a rapid response to the first 4 weeks of a CBT-E treatment. Discussion To our knowledge, this is the first study protocol describing a multicenter RCT to explore the three aforementioned objectives. Related risks in performing the study protocol have been outlined. The expected findings may serve as a guide for healthcare stakeholders to optimize ED care trajectories. Trial registration clinicaltrials.gov (NCT05812950).